Analysis of cleavage products of DNA repair enzymes and other nucleases. Characterization of an apurinic/apyrimidinic specific endonuclease from mouse plasmacytoma cells. - Haukanes, B I (1988)
We have developed a strategy by which the nature of phosphodiester bond breaks produced by various DNA-repair endonucleases and also other nucleases, can be characterized. A purified apurinic/apyrimidinic (AP) specific endonuclease from a permanently established mouse plasmacytoma cell-line (MPC-11) has been examined with respect to the exact incision site generated at the baseless site. By the aid of enzymatic treatment with calf intestinal phosphatase, the 3'-phosphatase activity of T4-polynucleotide kinase, chemical modification with piperidine in addition to the Maxam-Gilbert sequencing procedure, followed by separation on a DNA-sequencing gel, the nature of the cleaved phosphodiester bond, both 3' and 5' to the cleavage site, has been established. The AP-specific endonuclease investigated was classified as a class II AP-endonuclease according to the four possible classes of AP-endonuclease with respect to the termini produced. By use of this technique each single damaged and cleaved site can be investigated separately.